The device for training breathing of swimmers using of pneuma-vibration - Dychko, B.; Kochergin, A. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The development of new technologies of preparation of swimmers is one from major problems. The solution of this problem is possible at the expense application of special devices ensuring increase of efficiency of competitive exercise. Majorities of technical devices for preparation of swimmers are used for increase of special fitness of sportsmen. At the same time growth of sports results is possible at the expense of teleological effect on functional systems of an organism of the sportsmen. The device using of pneuma-vibration effect for training a respiratory system of swimmers in real swimming is offered. The offered device allows to increase volume of training work executed by swimmers in a specific space of time for simultaneous growth of adaptive possibilities of a swimmer's organism and to decrease the restoring time after the intensive training work.